2005
DOI: 10.1111/j.1440-1754.2005.00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug treatment of neonatal seizures by neonatologists and paediatric neurologists

Abstract: Australian and New Zealand neonatologists and paediatric neurologists generally use phenobarbitone to treat neonatal seizures presumed to be owing to hypoxic-ischaemic encephalopathy, though they do not always use appropriate doses. Neonatologists use phenobarbitone, phenytoin or a benzodiazepine for second and third episodes of seizures, whereas neurologists tend not to use benzodiazepines. Neonatologists use larger total doses of phenobarbitone than neurologists in pursuit of seizure control. Neonatologists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…11 An Australian study found that neonatologists were more likely to stop antiepileptic drugs within a few days of seizure cessation than neurologists (89% vs 56%). 3 These findings emphasize the need for further studies to determine the optimal length of treatment after neonatal seizures cease given the potential deleterious effects of antiepileptic drug treatment and seizure recurrence in the critical neonatal period.…”
Section: Discussionmentioning
confidence: 94%
“…11 An Australian study found that neonatologists were more likely to stop antiepileptic drugs within a few days of seizure cessation than neurologists (89% vs 56%). 3 These findings emphasize the need for further studies to determine the optimal length of treatment after neonatal seizures cease given the potential deleterious effects of antiepileptic drug treatment and seizure recurrence in the critical neonatal period.…”
Section: Discussionmentioning
confidence: 94%
“…On the basis of the simple BSA conversion method, a dose of phenobarbital between 200 and 250 mg/kg in mice, which has the ability to persistently induce the P450 gene expression, can be converted to a human equivalent dose between 15 and 20 mg/kg. This dose is equivalent to a loading dose of phenobarbital used to quickly produce blood levels to approximately 20 mg/ml for optimal anticonvulsant effects in the Food and Drug Administration's dose guidance for treatment of neonatal seizure by phenobarbital (Carmo and Barr, 2005;Lee et al, 2012). However, in a clinical application, using the BSA conversion from an animal species to human is inappropriate in many cases.…”
Section: Discussionmentioning
confidence: 99%
“…The Food and Drug Administration has a dose guidance to manage seizure with phenobarbital in neonates and infants. To quickly produce blood levels to approximate 20 mg/ml for optimal anticonvulsant effects, a much higher loading dose between 15 and 20 mg/kg is given by intravenous injection before a lower maintenance dose between 3 and 6 mg/kg/day is applied (Carmo and Barr, 2005;Lee et al, 2012). This has promoted us to reevaluate Dr. Shapiro's original studies in the context of a phenobarbital dosing regimen that is consistent with its clinical use in early life.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, these and other differences related to brain maturation might impact on the effect of antiepileptic drugs. Physicians continue to favor older AEDs to treat neonatal seizures, with phenobarbital being the drug of choice, followed by phenytoin and then benzodiazepines (3). Several of these choices (phenobarbital and the benzodiazepines) work by GABA mechanisms.…”
Section: Differences In Underlying Brain Functionmentioning
confidence: 99%